The Implementation of the Ungaran Artificial Insemination Center (IAC) Development Strategy with Business Model Canvas - Andiningtyas Mula Pertiwi; Harry Soesanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The success of a business is primarily determined by the development strategy undertaken. This study aims to develop alternative strategies for developing Artificial Insemination Centers to improve performance and income. The method used is descriptive qualitative with a case study approach. Data were collected through observation, documentation, and interview. The collected data were analyzed using SWOT analysis, and the results were elaborated into nine elements of the Business Model Canvas. The study results indicate that the strategy that has been carried out so far has been able to make IAC Ungaran achieve the set performance and income targets. In order to increase revenue streams, several strategies that need to be improvised are proposed, namely developing Key Partnerships, optimizing Key Resources, improving Customer Relationships by inviting cooperatives and private companies, and adding a Cost Structure to conduct development studies.